Evaluation of barley (Hordeum vulgare L.) genotypes for yield and yield attributing traits in Vindhyan Region of Uttar Pradesh - Challari Sai Chaitanya; Prashant Kumar Rai (Annals of Agricultural Research, 2025)
The present study at Field Experimentation Centre, Department of Genetics, SHUATS, Prayagraj during Rabi season of 2023-24 evaluated 20 Barley genotypes, including one check variety, for genetic variability, heritability, genetic advance and correlation. Twenty-three quantitative traits were analyzed, showing significant variation among genotypes. The highest yielding genotypes per plant in six row barley are IBT-51 (1.86 t), IBT-2 (1.80 t), IBT-31 (1.79 t), IBT-52 (1.73 t), IBT-25 (1.71 t), The highest yielded genotypes in two row barley among 6 genotypes are IBT-47 (1.48 t), IBT-20 (1.31 t), IBT-79 (1.31 t), IBT-72 (1.01 t), IBT-69 (0.99 t). The genotypic coefficient of variation was higher than the phenotypic coefficient of variation, with minimal differences between the two. GCV (%) values ranged between least of 0.70 (days to maturity) to a highest value of 32.74 (Grains per spike). PCV (%) followed a similar pattern had a range of 0.90 (days to maturity) to 32.84 (Grains per spike). The genotypic correlation coefficients for nearly all features surpassed the corresponding phenotypic correlation coefficients.